European Deposit Insurance Scheme(s) – Consequences for the EU’s Financial Stability - Zielińska-Lont, Klaudia (Comparative Economic Research. Central and Eastern Europe, 2021)
The aim of this paper is to evaluate the potential consequences that the shortcomings in harmonising the national deposit guarantee schemes may have on the financial stability of the European Union. The relevance of this subject is underlined both by the European Commission’s intention to revive the European Deposit Insurance Scheme project in 2021 and the recent signals from Germany that they are willing to support the initiative. The paper presents a review of the discussions on establishing a European Deposit Insurance Scheme, the reasons for the project’s failure and the consensus solution that took the form of the Deposit Guarantee Scheme Directive (DGSD). The limited scope of deposit guarantee scheme harmonisation under this directive is discussed in the context of the related EBA opinions pointing to different areas of potential improvements. Differences in national implementation are also reviewed in terms of their potential impact on financial stability. Apart from a careful literature review, statistical analysis of the available financial information characterizing the largest national deposit schemes of the euro is performed to quantify their progress towards the target level of the available financial means. The results prove that most national schemes are still far from reaching the 0.8% target level of readily available funds and that potentially desirable amendments to the DGSD may drag them even further away from reaching that target by 2024. The author concludes that from the perspective of financial stability, the EU should focus on establishing a single scheme at an international level that would complete the project of establishing a banking union. The results contribute to the ongoing discussion on the need to further integrate the national deposit guarantee schemes inside the EU.